2018
DOI: 10.2166/aqua.2018.075
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and contextualizing disinfection byproducts during the Flint Water Crisis: a case study and framework for broader application

Abstract: Total trihalomethanes (TTHMs) and other disinfection byproducts (DBPs) have been a concern in Flint, Michigan, in both delivered water and water from home water heaters. Historical TTHM data and DBP sampling results from Flint were combined with models for predicting hot water TTHMs to assess the probability of certain DBP concentrations. Results were compared with hot and cold water DBPs from a water system in Florida. Flint results were used to estimate cancer risk resulting from chronic exposure to hot wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Serious water quality problems arose in Flint, Mich., in 2014, after the City of Flint began distributing treated Flint River water from the Flint Water Service Center (FWSC) to the community. This is commonly referred to as the “Flint water crisis,” which has been documented in numerous publications including books (Clark , Hanna‐Attisha ), reports (USEPA , Michigan Civil Rights Commission ), and peer‐reviewed publications (e.g., Abernethy et al , Gómez et al , Goodwill et al , Pieper et al ).…”
mentioning
confidence: 99%
“…Serious water quality problems arose in Flint, Mich., in 2014, after the City of Flint began distributing treated Flint River water from the Flint Water Service Center (FWSC) to the community. This is commonly referred to as the “Flint water crisis,” which has been documented in numerous publications including books (Clark , Hanna‐Attisha ), reports (USEPA , Michigan Civil Rights Commission ), and peer‐reviewed publications (e.g., Abernethy et al , Gómez et al , Goodwill et al , Pieper et al ).…”
mentioning
confidence: 99%
“…11,[45][46][47][48] A few studies have assessed the impact of residential water heating systems on DBP formation and found that high temperatures, especially within water tanks, together with long stagnation times lead to an increase in THM and HAA concentrations relative to the cold water supply. [10][11][12][13]49,50 One study found that the concentration of dichloroacetonitrile (DCAN), the only chlorinated halcoacetonitrile detected in the study, was similar in cold water samples and hot water samples taken from tankless water heater systems. However, DCAN significantly decreased in hot tap water from traditional tank water heaters.…”
Section: Introductionmentioning
confidence: 86%
“…The resulting distasteful confrontation-between our citizen science team engaged in Flint and a non-profit backed by a high-profile Hollywood actor-did create negative publicity for Water Defense and Ruffalo, generating widespread national media coverage including The New York Times Magazine and other sources (Delaney 2016a; Delaney 2016b; Hohn 2016; Jerome 2016; Lynch 2016; Williams 2016). To further combat misinformation, we coordinated the 3 rd and 4 th party-independent EPA funded sampling events for DBPs in cold tap, hot tap, and shower water in Flint households, and eventually demonstrated that the DBP situation was completely normal (Allen et al 2017;Goodwill et al 2018). We also sought written scientific opinions and analytical reports from third-party academic water experts and assisted journalistic investigations into Mr. Smith's financial dealings (Allen et al 2017;Delaney 2016a;Johnson 2016b;Lynch 2016; Williams 2016; Roy 2017;Goodwill et al 2018).…”
Section: Water Defense Messaging On Bathing and Showering And Shigellmentioning
confidence: 99%
“…To further combat misinformation, we coordinated the 3 rd and 4 th party-independent EPA funded sampling events for DBPs in cold tap, hot tap, and shower water in Flint households, and eventually demonstrated that the DBP situation was completely normal (Allen et al 2017;Goodwill et al 2018). We also sought written scientific opinions and analytical reports from third-party academic water experts and assisted journalistic investigations into Mr. Smith's financial dealings (Allen et al 2017;Delaney 2016a;Johnson 2016b;Lynch 2016; Williams 2016; Roy 2017;Goodwill et al 2018). These efforts debunked many claims and compromised the reputation of Water Defense, but they also hardened loyalty to Water Defense among some Flint activists who would not acknowledge their unscientific approach.…”
Section: Water Defense Messaging On Bathing and Showering And Shigellmentioning
confidence: 99%